The motor neurons innervating the direct flight muscles of Drosophila melanogaster are morphologically specialized. - Trimarchi, J.R.; Schneiderman, A.M. (Journal of Comparative Neurology, 1994)
The anatomy of the motor neurons innervating six direct flight muscles in Drosophila melanogaster has been investigated by using a horseradish peroxidase backfilling technique. The somata of these motor neurons are arranged in two distinct clusters ipsilateral to the muscle they innervate. One cluster of cell bodies is located in the ventrolateral region between the prothoracic neuromere and the mesothoracic leg-related neuropil and the other is situated dorsally and posteriorly to the mesothoracic leg-related neuropil. Axons from somata in the ventrolateral cluster run in the anterior dorsal mesothoracic nerve, while axons from somata in the other cluster run in the mesothoracic accessory nerve. This distribution of somata and axons is discussed in the light of the morphological similarity and proximity of these functionally related muscles. On the basis of the branching patterns of their neurites, direct flight muscle motor neurons can be classified as stubbly, fibrous or tufted. The terminal arborizations of the motor neurons over the direct flight muscles are also morphologically specialized. Both the central and the peripheral morphological specializations of the direct flight muscle motor neurons correlate with the activity patterns exhibited by their associated muscles during flight and courtship song.